Review on Privacy Preservation on Big Data Using Map Reduce: Exploring Privacy Preservation Techniques in Big Data using Map Reduce (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Systematic literature review is one of the main research methodologies in research work. It outline the existing information about security dangers and to get the genuine reflection of the security techniques utilized in the current in Cloud Computing, and to give an edge work to recommend counter measures for the future challenges to be looked in Cloud Computing. Systematic reviews are based on a defined hunt procedure that intends to distinguish however much of the pertinent literature as could reasonably be expected. Main point of Privacy preservation in data mining is to find out such solution which will minimize the risk of abuse of the data. There are number of powerful techniques for privacy preserving data mining which have been proposed after broad study of data mining network as of late. In request to play out the privacy preservation, the vast majority of the technique utilizes some type of transformation on the original data. Here for this situation it is imperative to maintain the advantages of privacy preservation even after the changed dataset is made accessible for mining. In this paper we study about the previous studies done in the field of privacy preservation on big data using map reduce.